Site-specific Antibody-polymer Conjugates for siRNA Delivery - Lu, Hua (2013)
We describe here the development of site-specific antibody-polymer conjugates (APCs) for the selective delivery of small interference RNAs (siRNAs) to target cells. APCs were synthesized in good yields by conjugating an aminooxy-derivatized cationic block copolymer to an anti-HER2 Fab or full length IgG by means of genetically encoded para-acetyl phenylalanine (pAcF). The APCs all showed comparable binding affinity to HER2 as their native counterparts and no significant cellular cytotoxicity. Mutant S202-pAcF Fab and Q389-pAcF IgG polymer conjugates specifically delivered siRNAs to HER2(+) cells and mediated potent gene silencing at both the mRNA and protein levels. However, a mutant A121-pAcF IgG polymer conjugate, despite its high binding affinity to HER2 antigen, did not induce a significant RNA interference response in HER2(+) cells, presumably due to steric interference with antigen binding and internalization. These results highlight the importance of conjugation site on the activity of antibody-polymer based therapeutics and suggest that such chemically-defined APCs may afford a useful targeted delivery platform for siRNAs or other nucleic acid based therapies.